RETRACTION Polevoy, G. (2024). Métodos de rehabilitación física de escolares de 15 a 17 años con osteocondrosis cervical (Methods of physical rehabilitation of schoolchildren aged 15-17 with cervical osteochondrosis). Retos, 58, 282–290. https://doi.org/10.47197/retos.v58.106352 - RETOS, RETOS (Retos, 2025)
Polevoy, G. (2024). Métodos de rehabilitación física de escolares de 15 a 17 años con osteocondrosis cervical (Methods of physical rehabilitation of schoolchildren aged 15-17 with cervical osteochondrosis). Retos, 58, 282–290. https://doi.org/10.47197/retos.v58.106352 Retraction of the article by the editor of the journal. Due to plagiarism by the author.